South Africa's pursuit for a National Minimum Wage: a double edged sword - Masipa, T. S. (SAAPAM (South African Association of Public Administration and Management), 2016)
It is a historical fact that the democratic South Africa inherited the country with the triple challenges of unemployment, poverty and inequality. Majority of blacks became the victims of such inheritance and they often demonstrate their discontent via protests which for the last decade painted South Africa as a theatre of social unrests. A national minimum wage is believed to be amongst the solutions to close the gap of inequalities, with the view that minimum wages will move the poor workers out of poverty and improve their standards of living. It is within this context the purpose of this paper is to determine the impact of minimum wage on employment in South Africa. The theoretical framework adopted in this paper is the general equilibrium approach. From the analysis, the paper argues that though the imposition of minimum wages is likely to improve the living conditions of the poor worker, by moving them out of poverty, they may however pose a threat of job losses in a sense that employers are likely to respond by reducing or retrenching workers to cover for the high costs of labour. The paper therefore concludes that the imposition of minimum wages in the labour market requires a critical analysis, not a blanket approach as this may result in job losses, and thus widen poverty and inequality. Given that majority of the poor people in South Africa are either self-employed or in informal sector, of which the minimum wage legislation doesn't cover, this sadly implies that the majority of the poor working class are likely not to benefit any prospects of minimum wage imposed. The paper therefore recommends that any minimum wage legislation should be designed in such a way that it also protects and benefit those who are in informal sectors. More importantly, government must enhance its mechanisms to ensure that employers comply with the imposed minimum wage legislation.
Article
Keywords: Minimum wage; Employment; Poverty; Inequality; Minimum wage -- South Africa; Employment (Economic theory); Poverty